Complete chloroplast genome of a Peruvian landrace of Cucurbita moschata, loche, and its comparative analysis with other relative species - Saldaña Serrano, Carla Liset; Estrada Cañari, Richard; Suca, Esther; Cruz Grimaldo, Camila Leandra; Vilcara, Edgardo; Arbizu Berrocal, Carlos Irvin (Research Square, 2025)
Background Loche (Cucurbita moschata) is a pre-Columbian squash that is cultivated exclusively in the northern coast of Peru, Lambayeque. This crop is notable for the presence of warts in its skin and for its vegetative reproduction as it commonly lacks of seeds in fruits. Currently, loche may be considered a new product for international markets, recognizing the gastronomy of Lambayeque in the world and dynamizing the Peruvian agro-export area. However, genomic information about this squash is very limited.